Perlindungan Hukum terhadap Mantan Narapidana dalam Perspektif Undang-undang Ketenagakerjaan - I Made Deni Pramudya Adi Putra; Anak Agung Sagung Laksmi Dewi; I Wayan Arthanaya (Jurnal Preferensi Hukum, 2022)
An former convict is very difficult to get a job. Many companies and jobs are very difficult to accept an ex-convict because an ex-convict must have a bad view or discrimination from society. The purposes of this research are to reveal the right of former convicts to get a job when viewed from the Manpower Act No. 13 of 2003 and the legal protection of former convicts who are discriminated against to get a job. The method used in this research is normative legal research with a statutory approach and a conceptual approach. The collection technique was carried out using library techniques. The sources of legal materials used are primary and secondary sources of legal materials which are analyzed qualitatively and presented in descriptive form. The research findings reveal that the provisions of Articles 5 and 6 of Law Number 13 of 2003 concerning Manpower imply that everyone, including a former convict, has the right to opportunity and is treated fairly in the eyes of the law and society without any act of discrimination. Forms of legal protection are direct or indirect and can be in the form of preventive and repressive legal protection. The perpetrators who commit acts of discrimination are charged with criminal sanctions as regulated in Article 156 of the Criminal Code.